2013
DOI: 10.1002/adma.201204944
|View full text |Cite
|
Sign up to set email alerts
|

DNA‐Guided Metal‐Nanoparticle Formation on Graphene Oxide Surface

Abstract: A simple and universal route for the preparation of metal–graphene oxide (GO) heterostructures with controllable nanoparticle size and shape using double‐stranded DNA (dsDNA) as a template is reported. This proof‐of‐concept work successfully demonstrates that dsDNA can be adsorbed onto GO to create biocompatible and easily functionalizable Ag–GO, Au–GO, Cu–GO, Pt–GO, and Au/Cu/Pt–GO heterostructures using the same experimental conditions for each of the multicomposite nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
74
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(80 citation statements)
references
References 48 publications
(53 reference statements)
2
74
0
1
Order By: Relevance
“…Interestingly, NP-GO NCs exhibit enhanced surface enhanced Raman scattering, catalytic, and antibacterial properties compared to bare GO and NP. [208][209][210][211][212][213] Recent studies reported the fabrication of AgNPs-decorated GO as an effective antibacterial agent. [213][214][215][216] Synthesis of AgNPs decorated on magnetic GO NCs was demonstrated, which showed highly effective inhibitory property and reusability even at the very low concentration (12.5 ppm).…”
Section: Synthesis Of Agnps By Proteins and Dnamentioning
confidence: 99%
“…Interestingly, NP-GO NCs exhibit enhanced surface enhanced Raman scattering, catalytic, and antibacterial properties compared to bare GO and NP. [208][209][210][211][212][213] Recent studies reported the fabrication of AgNPs-decorated GO as an effective antibacterial agent. [213][214][215][216] Synthesis of AgNPs decorated on magnetic GO NCs was demonstrated, which showed highly effective inhibitory property and reusability even at the very low concentration (12.5 ppm).…”
Section: Synthesis Of Agnps By Proteins and Dnamentioning
confidence: 99%
“…[6][7][8] Furthermore, the chemical reactivity of 2D materials such as graphene oxide (GO) and TMDs has raised concerns and novel templates have been proposed to fabricate functional composites. [9][10][11][12][13][14][15][16][17] Black phosphorus (BP) has emerged to be an exciting member of the 2D family. 18,19 BP has strong in-plane bonds in conjunction with weak van der Waals interlayer interactions thereby enabling exfoliation into few-layer BP sheets or phosphorene (single-layer BP).…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] Many DNA-related enzymes were also involved to introduce functions such as signal amplification. 16,17 Finally, DNA/GO conjugates were used to template materials synthesis such as metal nanoparticles, [18][19][20] and stacked GO sheets. 21 Fundamental studies on the interaction between DNA and GO were also carried out.…”
Section: Introductionmentioning
confidence: 99%